Uma proposta de ensino fundamentada no desenvolvimento do pensamento geométrico segundo a teoria de Van Hiele - (:unkn) unknown (Universidade Federal do Pampa, 2022)
Flat geometry is a very important subarea of knowledge and with a great deal of employability in the social context, however, it is little worked on in schools and often its development is due to memorization. The flat geometry has fundamental concepts for the other subareas of mathematics and among these, the focus of this work was the concepts of area and perimeter. Our proposal aims to analyze how students enrolled in the Component of Mathematics Teaching Laboratory III perceive the development of teaching sequences based on the development of geometric thinking according to Van Hiele's Theory, when working concepts of area and perimeter with elementary school students. Our target audience was the students of the 5th semester of the Federal University of Pampa, Itaqui campus. The Work was applied during the month of July 2022, where the contents developed were the area and perimeter of flat figures from a teaching sequence, thought from the first three levels of van Hiele's model. The results indicate that students have difficulties in working with activities that run away from traditional teaching, it is also possible to perceive in some students confusion to differentiate area and perimeter during the application of the sequence, but state that although the activity is differentiated, quite complex and make them reflect, it is very interesting because it allows learning outside the traditional context.
Keywords: Sequência de ensino; Van Hiele; Área; Perímetro; Teaching sequence; Perimeter; CNPQ::CIENCIAS EXATAS E DA TERRA